PENINGKATAN KEAMANAN DATA TEKS TERENKRIPSI ALGORITMA LUCIFER MENGGUNAKAN STEGANOGRAFI GIFSHUFFLE PADA CITRA - Dian Anggara; Abdul Sani Sembiring (STMIK Budi Darma, 2019)
Increased resistance to the algorithm used to secure secret messages is very necessary. This is caused by the ability of the attackers who are able to justify various ways to solve the algorithm used to secure data. Lucifer algorithm has many variants, one of which is a lucifer with a 16-round feistel network that operates on 128 bit blocks and uses 128-bit keys. Computing 2 ^ 36 plaintext and 2 ^ 36 complexity can attack this variant. This study describes the use of the gifshuffle algorithm to optimize the Lucifer algorithm in securing data. The gifshuffle algorithm is used to hide encrypted messages based on the Lucifer algorithm into the gif format media. Based on tests conducted, it was found that there were no significant differences in the cover image and stegano image after the message insertion process was carried out.Keywords: Cryptography, Steganography, Lucifer, Gifshuffle, message